MANAJEMEN PERSEDIAAN DAN KINERJA UKM DI SEKTOR MANUFAKTUR DI KOTA MAKASSAR - Kendek, Yohanis Sampe; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Ramlawati, Ramlawati (JURNAL ILMIAH EDUNOMIKA, 2024)
The research evaluated inventory management (IM) strategies employed by small and medium-sized enterprises (SMEs) in Makassar City manufacturing sector, Indonesia. The study drew its participants from industrial zones including Sudiang, Perintis, Bumi Taman Permai, and Uripsumuarjo. Respondents were purposefully selected from companies within these areas. A qualitative, descriptive research design was adopted, utilizing purposive sampling. From a sample size of 244 participants, data was gathered through completed questionnaires. The study revealed that the majority of SMEs rely on the Just-In-Time (JIT) inventory management approach, with limited familiarity with other computerized inventory systems. Given the reliance on JIT, SMEs experience supply chain difficulties, as they must maintain consistent communication with suppliers and minimize material delivery times. However, due to a lack of computerized systems, orders are often placed only when needed, causing delays for customers. Based on these findings, the researchers suggested that further research be conducted to explore specific areas in greater depth.